2015
DOI: 10.1097/01.sa.0000469979.96619.10
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Postoperative Bleeding and Outcomes in Neonates Undergoing Cardiopulmonary Bypass

Abstract: T he effects of dexmedetomidine premedication on the minimum alveolar concentration of sevoflurane for tracheal intubation (MAC TI ) in children was investigated in a prospective, randomized, clinical comparison study in the operating room of an academic hospital in 90 pediatric, American Society of Anesthesiologists physical status I patients, aged 3 to 7 years. The patients, who were scheduled for minor surgery, were randomized into 3 groups who received placebo, dexmedetomidine 1 μg/kg or dexmedetomidine 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…Perioperative bleeding following cardiopulmonary bypass (CPB) is associated with significant morbidity and mortality. 1,2 Compared to older children and adults, neonates have an increased risk of bleeding during and after CPB. 3 5 Excessive bleeding after neonatal cardiac surgery has been linked to increased need for postoperative dialysis, extracorporeal membrane oxygenation, cardiac intensive care unit length of stay, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative bleeding following cardiopulmonary bypass (CPB) is associated with significant morbidity and mortality. 1,2 Compared to older children and adults, neonates have an increased risk of bleeding during and after CPB. 3 5 Excessive bleeding after neonatal cardiac surgery has been linked to increased need for postoperative dialysis, extracorporeal membrane oxygenation, cardiac intensive care unit length of stay, and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A negative correlation between platelet transfusion and CMP suggested that pediatric patients under CMP have a lower intraoperative demand for platelet products. According to Guzzetta et al, 31 long CPB time and serious coagulation damage both contribute to more postoperative chest tube drainage and delayed extubation. In this study, we found that CPB time was positively correlated with delayed extubation rate.…”
Section: F I G U R Ementioning
confidence: 99%
“…Given the promising developments of peptide mimetic drugs for regulating hemostasis and thrombosis, these drugs could prove to be attractive targets for the application of novel therapeutics in emerging markets. One such an example is the treatment of postoperative bleeding in neonatal populations [Guzzetta et al, ]. Mitigating postoperative bleeding is currently addressed through transfusion of adult blood products, including platelets and cryoprecipitate (fibrinogen component) [Brown et al, ].…”
Section: Future Directions/emerging Marketsmentioning
confidence: 99%